Students’ Difficulties in Reading Comprehension at the Ninth Grade MTs Negeri 1 Manado - Kaharuddin, Nikmala N; Thaib, Dhea Ramadanti (Journal of English Language Teaching, Linguistics, and Literature Studies, 2023)
This research aims to identify the difficulties faced by students in reading and thecauses of these difficulties. The researcher employed a mixed-methods research(MMR) approach, utilizing four research instruments: observation, interviews, tests,and documentation. The sample for this research consisted of 30 students from class9-C and two English teachers from class 9 of MTs Negeri 1 Manado. There were threedata collection procedures. The first procedure involved the researcher observingclass 9-C. The second procedure included the administration of a multiple-choice testwith 10 questions to the students of class 9-C. The third procedure involvedconducting interviews with 30 students and 2 English teachers regarding the causesof students' difficulties in reading. Based on the research findings, the researcheridentified four difficulties that students face in understanding reading: limitedvocabulary with a percentage of 68.33%, drawing conclusions 60%, detailscomprehension 54.16%, and grasping the main idea 50%. There were two factorscausing students' difficulties: internal factors and external factors. Internal factorsincluded students not reading enough, texts in English, limited vocabulary, andstudent laziness. External factors included a lack of English books and students notbringing dictionaries.Keywords: Student difficulties, Reading comprehension, Internal and External Factor